2022
DOI: 10.3389/fphar.2021.775328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Epileptic Encephalopathy Caused by KCNMA1 Loss-of-Function Mutations

Abstract: The gene kcnma1 encodes the α-subunit of high-conductance calcium- and voltage-dependent K+ (BK) potassium channel. With the development of generation gene sequencing technology, many KCNMA1 mutants have been identified and are more closely related to generalized epilepsy and paroxysmal dyskinesia. Here, we performed a genetic screen of 26 patients with febrile seizures and identified a novel mutation of KCNMA1 (E155Q). Electrophysiological characterization of different KCNMA1 mutants in HEK 293T cells, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…37 Yao et al reported another de novo LOF KCNMA1 variant, p.(E155Q), in a Liang-Wang syndrome patient with febrile seizures, hyperactivity, repeated daze, poor language development and developmental delay. 38 In summary, in this study, we characterized four new patients with KCNMA1 variants, including p.(A172T), p.(A314T), p.(N536H) and p.(N995S), in detail. We found that two of these variants, p.(A172T) and p.(A314T), acted by a LOF mechanism, and were associated with Liang-Wang syndrome.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…37 Yao et al reported another de novo LOF KCNMA1 variant, p.(E155Q), in a Liang-Wang syndrome patient with febrile seizures, hyperactivity, repeated daze, poor language development and developmental delay. 38 In summary, in this study, we characterized four new patients with KCNMA1 variants, including p.(A172T), p.(A314T), p.(N536H) and p.(N995S), in detail. We found that two of these variants, p.(A172T) and p.(A314T), acted by a LOF mechanism, and were associated with Liang-Wang syndrome.…”
Section: Discussionmentioning
confidence: 94%
“…Graber et al reported a de novo heterozygous one bp deletion variant in KCNMA1 (c.112delG) in a Liang–Wang syndrome patient who presented with drug‐resistant epilepsy with severe developmental delay initially related to bilateral asymmetric frontal polymicrogyria since the age of 2 months 37 . Yao et al reported another de novo LOF KCNMA1 variant, p.(E155Q), in a Liang–Wang syndrome patient with febrile seizures, hyperactivity, repeated daze, poor language development and developmental delay 38 …”
Section: Discussionmentioning
confidence: 99%
“…However, since half of those harboring LOF variants also report seizures (Liang et al ., 2019; Miller et al ., 2021), including the H444Q and individuals with putative truncation alleles, Kcnma1 H444Q/WT and Kcnma1 —/— mice were assessed in parallel. No seizures have been previously reported in two established Kcnma1 —/— mouse models (Bailey et al ., 2019; ALM unpublished data), but spontaneous epilepsy was reported in a CRISPR-exon4 Kcnma1 —/— line (Yao et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are no patients with homozygous KCNMA1 alleles validated as functionally null for channel activity (Miller et al ., 2021), but the ataxia, tremor, decreased strength, and hyperactivity in Kcnma1 —/— mice (Imlach et al ., 2008; Meredith et al ., 2004; Sausbier et al ., 2004; Typlt et al ., 2013; Wang et al ., 2020) are symptoms observed at lower incidence among patients. Lastly, our experimental conditions failed to corroborate the influence of LOF alleles on seizure propensity predicted from several animal studies (Ermolinsky et al ., 2008; Kuebler et al ., 2001; Pacheco Otalora et al ., 2008; Sheehan et al ., 2009; Shruti et al ., 2008; Yao et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5 F, G). Knockout of Kcnma1 leads to autophagic dysfunction [ 44 ]. Therefore, these findings suggest that Mef2d mediates VSMC autophagy by regulating the cGMP-PKG signalling pathway.…”
Section: Discussionmentioning
confidence: 99%